2015
DOI: 10.1590/0100-69912015001006
|View full text |Cite
|
Sign up to set email alerts
|

Resection of liver metastasis from neuroendocrine tumors: evaluation of results and prognostic factors

Abstract: Results ResultsResults Results: twelve patients were male and ten female, with a mean age of 48.5 years. Bilobar disease was present in 17 patients (77.3%). In ten patients (45.5%) the primary tumor originated in the pancreas, terminal ileum in eight, duodenum in two, rectum in one and jejunum in one. Complete surgical resection (R0) was achieved in 59.1% of patients. Eight patients (36.3%) developed complications in the immediate postoperative period, one of them dying from septicemia. All patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…While management strategies for NELM include non‐surgical approaches such as intra‐arterial (IAT) or systemic targeted agents, as well as octreotide and tyrosine kinases inhibitors, surgery offers the best potential for cure . Surgical resection of NELM has been associated with 5‐year OS ranging from 61% to 76% and 10‐year survival of 35% to 51% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While management strategies for NELM include non‐surgical approaches such as intra‐arterial (IAT) or systemic targeted agents, as well as octreotide and tyrosine kinases inhibitors, surgery offers the best potential for cure . Surgical resection of NELM has been associated with 5‐year OS ranging from 61% to 76% and 10‐year survival of 35% to 51% .…”
Section: Introductionmentioning
confidence: 99%
“…7 While management strategies for NELM include non-surgical approaches such as intra-arterial (IAT) or systemic targeted agents, [8][9][10][11][12][13][14] as well as octreotide and tyrosine kinases inhibitors, [11][12][13] surgery offers the best potential for cure. 6,15,16 Surgical resection of NELM has been associated with 5-year OS ranging from 61% to 76% and 10-year survival of 35% to 51%. 17,18 Our group had previously reported that statistical cure following resection of NELM was 44% within 5.1 years after surgery.…”
mentioning
confidence: 99%
“…The possible reason is that hNENs are transferred from different sources. The blood flow supply composition is different, which results in a different washout time than HCC[21,22]. In addition, the proportions of CEUS characteristics, including enhancement of arterial phase, portal venous phase, and enhancement of late phase, enhancement forms, tumor vasculature, tumor necrosis, and capsule enhancement, were similar in the hNEN and HCC groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic resection was a treatment of choice for neuroendocrines tumor of the liver ( 5 ). Neuroendocrine tumors, have although considered slow growing tumors and mildly aggressive, tend to develop distant metastatic disease with relative frequency, and the liver was the most affected organ ( 6 ). For patients with restricted but unresectable liver disease, transplantation has appeared to be the best therapeutic alternative ( 7 ).…”
Section: Discussionmentioning
confidence: 99%